Excessive day time sleepiness and its associated factors among adult population in an urban area of southern Rajasthan - Nitesh Mangal; Mansi Sharma; Mehul Patel; Dilip Kumar L; Varghese KA; Rajkumar Patil (Asian Journal of Medical Sciences, 2023)
Background: Sleep problems have been considered as an unmet public health problem. Sleep problems are mostly under reported and neglected by the Indian population. Very limited studies have been conducted in India on this aspect. Aims and Objectives: The aim of the study was to estimate the prevalence of excessive day time sleepiness (EDS) and its associated factors among urban adult population. Materials and Methods: A community based cross-sectional study was conducted among 409 adults of 20–60 years age group in urban Udaipur. Socio-demographic and other details were obtained using a semi structured questionnaire. Using Epworth Sleepiness Scale, assessment of EDS was assessed. Results: In the present study, mean age of the participants was 40.8 ± 11.3 years. Considering the ESS score of 10 or more, EDS was observed in 60.2% subjects. EDS was associated with age, gender, milk consumption, and mobile use. No significant association was found between EDS with central obesity, body mass index, marital status, literacy, occupation, exercise, smoking, and consumption of alcohol. Conclusion: In the present study, the prevalence of EDS was high. Therefore, early identification of excessive sleep problems and appropriate intervention that address the various determinants of the sleep problems is of prime importance.